Cecropin D-derived synthetic peptides in the fight against Candida albicans cell filamentation and biofilm formation - Guevara-Lora, Ibeth; Bras, Grazyna; Juszczak, Magdalena; Karkowska-Kuleta, Justyna; Gorecki, Andrzej; Manrique-Moreno, Marcela; Dymek, Jakub; Pyza, Elzbieta; Kozik, Andrzej; Rapala-Kozik, Maria (Frontiers in Microbiology, 2023)
The recent progressive increase in the incidence of invasive fungal infections, especially in immunocompromised patients, makes the search for new therapies crucial in the face of the growing drug resistance of prevalent nosocomial yeast strains. The latest research focuses on the active compounds of natural origin, inhibiting fungal growth, and preventing the formation of fungal biofilms. Antimicrobial peptides are currently the subject of numerous studies concerning effective antifungal therapy. In the present study, the antifungal properties of two synthetic peptides (ΔM3, ΔM4) derived from an insect antimicrobial peptide ‒ cecropin D ‒ were investigated. The fungicidal activity of both compounds was demonstrated against the yeast forms of C. albicans, C. tropicalis, and C. parapsilosis, reaching a MFC99.9 in the micromolar range, while C. glabrata showed greater resistance to these peptides. The scanning electron microscopy revealed a destabilization of the yeast cell walls upon treatment with both peptides; however, their effectiveness was strongly modified by the presence of salt or plasma in the yeast environment. The transition of C. albicans cells from yeast to filamentous form, as well as the formation of biofilms, was effectively reduced by ΔM4. Mature biofilm viability was inhibited by a higher concentration of this peptide and was accompanied by increased ROS production, activation of the GPX3 and SOD5 genes, and finally, increased membrane permeability. Furthermore, both peptides showed a synergistic effect with caspofungin in inhibiting the metabolic activity of C. albicans cells, and an additive effect was also observed for the mixtures of peptides with amphotericin B. The results indicate the possible potential of the tested peptides in the prevention and treatment of candidiasis.